A method for directly evaluating the adaptability of plant fibers in cement slurry under high temperature and high pressure

By curing plant fiber materials in high-temperature and high-pressure water loss instruments and muffle furnaces, and conducting X-ray diffraction and thermogravimetric analysis tests, the adaptability of plant fibers in cement slurry under high temperature and high pressure was solved, and the problem of difficulty in authentically evaluating plant fibers in the prior art was solved, and the accurate evaluation of plant fiber adaptability was achieved.

CN115508171BActive Publication Date: 2025-05-02JIAHUA SPECIAL CEMENT +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211087647.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-07
Publication Date
2025-05-02
Estimated Expiration
2042-09-07

AI Technical Summary

Technical Problem

The prior art lacks a method to directly evaluate the adaptability of plant fibers in cement slurries under high temperature and high pressure, and it is difficult to truly evaluate the adaptability of plant fibers in cementing engineering environments.

Method used

By preparing cementing cement slurry and heating it in a high-temperature and high-pressure water loss meter, the filtrate was obtained for wetting the plant fiber material, placed in a muffle furnace for high-temperature maintenance, and then X-ray diffraction and thermogravimetric analysis tests were performed to compare the crystallinity and mass loss curves of the plant fiber material to evaluate its adaptability.

Benefits of technology

This method can effectively evaluate the adaptability of plant fibers of various sizes in cement slurry under high temperature and high pressure. By directly testing the crystal structure, chemical structure and thermal stability of plant fibers, it provides accurate data to support the application of plant fibers in oil and gas well cementing engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115508171B_ABST
    Figure CN115508171B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for directly evaluating the adaptability of plant fibers in cement slurry under high temperature and high pressure, which belongs to the technical field of petroleum and natural gas cementing engineering materials, including cement slurry preparation, high temperature and high pressure dehydration instrument maintenance, filtrate preparation, plant fiber material input, muffle furnace high temperature maintenance, filtration and washing, water removal, plant fiber structure testing, thermal stability testing and judgment. The present invention can effectively evaluate the adaptability of plant fibers of various sizes in cement slurry under high temperature and high pressure, and the method is simple. By directly testing the crystal structure, chemical structure and thermal stability of plant fibers under different maintenance conditions, the adaptability of plant fibers can be intuitively and accurately obtained, which provides data support for the application of plant fibers in oil and gas well cementing engineering and has important significance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of petroleum and natural gas cementing engineering materials, and in particular relates to a method for directly evaluating the adaptability of plant fibers in cement slurry under high temperature and high pressure. Background Art

[0002] Cement-based composite materials refer to composite materials that use silicate cement as the matrix, alkali-resistant glass fiber, general synthetic fiber, various ceramic fibers, high-performance fibers such as carbon and aramid, metal wire, natural plant fiber and mineral fiber as reinforcement, and are added with fillers, chemical additives and water through a composite process. They have been widely used in construction, oil and gas well cementing and other projects. Although cement-based composite materials have high compressive strength, their elastic deformation capacity and tensile strength are low. In a large number of studies on improving the elastic deformation and tensile strength of cement-based composite materials, it was found that fiber is one of the most effective ways to improve its elastic deformation and tensile strength. Among the many fiber materials, plant fibers and cellulose fibers prepared from plant fibers are widely concerned and applied as renewable resources.

[0003] Cellulose fiber is the main component of plant fiber. Because its molecular chain contains a large number of hydroxyl groups and has strong intermolecular hydrogen bonds, it exhibits excellent tensile strength and good hydrophilicity. It is considered to be one of the effective materials for improving the performance of cement paste (rheology, water bleeding and hydration process) and improving the mechanical properties of cement paste. For example, scholars (J. Goncalves, Y. Boluk, V. Bindiganavile. Turbidity-based measurement of bleeding in fresh cement paste as affected by cellulose nanofibers [J], Cement & Concrete Composites. 2021, 123: 104197.) found that the rheological properties of cement paste such as yield stress and plastic viscosity can be effectively improved by modifying plant fibers by TEMPO oxidation. At the same time, there are also a large number of reports on the effects of plant fibers and cellulose fibers on the mechanical properties of cement paste. (X. Xie, Z. Zhou, Y. Yan, Flexural properties and impact behavior analysis of bamboo cellulosic fibers filled cement based composites, Constr. Build. Mater. 220 (2019) 403-414.) It was found that plant fibers can increase the fracture toughness and absorbed energy of cement paste by 2.7~45.9 times and 2~24 times. This shows that plant fibers can greatly improve the comprehensive performance of cement-based materials. At present, with the development of deep oil and gas and shale oil and gas resources, higher requirements are put forward for the performance of cementing cement slurry and cement paste. The use of plant fibers to improve the comprehensive performance of cementing cement slurry and cement paste has great application potential and is in line with the concept of green and environmentally friendly economic development. However, in oil and gas well cementing projects, cementing cement slurry often needs to serve under high temperature and high pressure. At present, there is little research on the temperature resistance of plant fibers, and there is also a lack of evaluation methods for the adaptability of plant fibers in cement slurry environments under high temperature and high pressure.

[0004] Currently, the adaptability of plant fibers is mostly evaluated by indirect evaluation methods. For example, the patent publication number is CN113049382A, and the patent name is a method for in-situ characterization of the performance degradation of plant fibers in a cement matrix environment. By testing the changes in the pull-out force of plant fibers from the cement matrix, the performance degradation of plant fibers in the cement matrix environment is indirectly characterized; another example is (Saulo Rocha Ferreira, Luiz Eduardo Silva, Zach McCaffrey, et al. Effect of elevated temperature on sisal fibers degradation and its interface to cement based systems [J]. Construction and Building Materials, 2021, 272: 121613), which uses a muffle furnace to directly cure plant fibers at high temperature and observe the changes in plant fiber performance and microstructure to evaluate the adaptability of plant fibers. The main problems of these methods are as follows: (1) The method of testing the pull-out force of plant cellulose fibers is only applicable to evaluating the adaptability of long-sized plant fibers. However, since cementing projects are underground concealed operations and short-sized fiber materials are often used, long-sized plant fibers will block the check valve and cause cementing failure. At the same time, this method indirectly evaluates the adaptability of plant fibers by testing the interface pull-out strength between plant fibers and cement stone matrix, and cement-based materials themselves are time-varying materials. Therefore, it is difficult to directly reflect the adaptability of plant fibers; (2) The high-temperature environment directly maintains plant fibers, and the simulated environment is greatly different from the high alkalinity and high mineralization environment of cementing cement slurry. The glycosidic bonds in plant fibers are easily broken in high temperature and strong alkaline environments, destroying the plant fiber structure; this method is difficult to truly evaluate the adaptability of plant fibers in cementing engineering environments. Therefore, it is urgent to establish an evaluation method for the adaptability of plant fibers in cementing cement slurry under high temperature and high pressure to provide technical means for optimizing plant fiber materials suitable for oil and gas well cementing projects. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for directly evaluating the adaptability of plant fibers in cement slurry under high temperature and high pressure, so as to at least solve part of the above technical problems.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A method for directly evaluating the adaptability of plant fibers in cement slurry under high temperature and high pressure comprises the following steps:

[0008] Step 1, cement slurry preparation: preparing cementing cement slurry, and heating the cementing cement slurry under normal pressure;

[0009] Step 2, high temperature and high pressure dehydration instrument maintenance: transfer the cement slurry heated in step 1 to the high temperature and high pressure dehydration instrument, seal it and then heat it;

[0010] Step 3, filtrate preparation: remove and collect the filtrate in the cementing slurry in the high temperature and high pressure dehydration instrument after reheating;

[0011] Step 4, putting the plant fiber material into the high temperature and high pressure curing tank, pouring the filtrate into the plant fiber material to wet it, and sealing the high temperature and high pressure curing tank;

[0012] Step 5, high temperature curing in a muffle furnace: placing the sealed high temperature and high pressure curing tank in a muffle furnace for curing;

[0013] Step 6, filtration and washing: taking out the high temperature and high pressure curing tank after curing from the muffle furnace, cooling it to room temperature, pouring out the mixture of the plant fiber material and the filtrate inside, and filtering and washing out the plant fiber material;

[0014] Step 7, dehydration: vacuum freezing to remove free water in the plant fiber material to obtain the cured plant fiber material;

[0015] Step 8, plant fiber structure test: using an X-ray diffractometer to collect the X-ray diffraction spectrum of the plant fiber material after curing, and calculating the crystallinity of the plant fiber material after curing;

[0016] Step 9, thermal stability test: using a thermogravimetric analyzer to test the mass loss curve of the plant fiber material after curing;

[0017] Step 10, determination: compare the X-ray diffraction pattern and crystallinity obtained in step 8 and the mass loss curve obtained in step 9 with the X-ray diffraction pattern, crystallinity and mass loss curve of the plant fiber material that has not been treated with high pressure and high temperature, and evaluate whether the plant fiber material meets the requirements of cement slurry under high temperature and high pressure.

[0018] Furthermore, in step 1, cementing slurry is prepared according to GB / T19139-2012 standard; preferably, the cementing slurry is heated by a normal pressure viscosifier, the heating temperature is room temperature to 90° C., and the heating time is 10 to 30 minutes, preferably 20 minutes.

[0019] Furthermore, in step 2:

[0020] When the reheating experimental temperature is room temperature to 100°C, pour the cement slurry heated in step 1 into a high temperature and high pressure dehydration apparatus, seal it, and cure it for 30 to 90 minutes, preferably 60 minutes;

[0021] When the reheating test temperature is 100-210°C, pour the cement slurry heated in step 1 into the high temperature and high pressure dehydration apparatus, seal it, and inject a pressure greater than the saturated vapor pressure of water at the test temperature into the high temperature and high pressure dehydration apparatus, and maintain it for 30-90 minutes, preferably 60 minutes.

[0022] Furthermore, in step 3, the filtrate hole at the bottom of the high-temperature and high-pressure dehydration instrument is opened, and nitrogen or inert gas is introduced into the top of the high-temperature and high-pressure dehydration instrument to make its internal pressure reach 0.1-6.9 MPa, and the filtrate in the cementing cement slurry is removed and collected by using the pressure difference;

[0023] Preferably, when the reheating experimental temperature is 100-210°C, a condenser is connected to the filtrate hole at the bottom of the high temperature and high pressure dehydration apparatus to condense and collect the filtrate.

[0024] The purpose of step 1 to step 3 of the present invention is to obtain filtrate for high temperature curing of plant fibers. Therefore, the preparation conditions of the filtrate simulate the preparation of high temperature cement slurry.

[0025] Furthermore, in step 4, the amount of plant fiber material input is 1-2 g, the amount of filtrate poured into the cementing slurry is 100-150 mL, and the plant fiber material is any one of bamboo fiber, cotton fiber, sisal fiber, wood fiber or crop straw fiber.

[0026] Furthermore, in step 5, the muffle furnace curing temperature and time are matched with the cementing engineering environment. Preferably, the muffle furnace curing temperature is room temperature to 210° C., and the curing time is 0 to 180 days, more preferably 1-180 days, and further preferably 14-60 days.

[0027] Furthermore, in step 6, a vacuum filter is used to filter out the filtrate in the mixture to obtain the plant fiber material, and distilled water is continuously used for washing during the filtration process until the pH value of the filtrate drops to 7.

[0028] Furthermore, in step 8, the operating voltage of the X-ray diffractometer is 40 kV, the operating current is 30 mA, the scanning rate is 0.02° / s, the scanning range is 5-40°, and the crystallinity is calculated according to the Segal empirical model. The Segal empirical model is ,in I (002) is the maximum intensity of the lattice diffraction angle, I am is the scattered intensity of the non-crystalline background diffraction.

[0029] Furthermore, in step 9, the heating rate of the thermogravimetric analyzer is 10°C / min, and the test temperature is 40-400°C.

[0030] Furthermore, in step 10, if the X-ray diffraction pattern and crystallinity obtained in step 8 and the mass loss curve obtained by testing in step 9 are respectively the same as the X-ray diffraction pattern, crystallinity and mass loss curve of the plant fiber material that has not been treated with high pressure and high temperature, the plant fiber material meets the requirements of cementing slurry under high temperature and high pressure; otherwise, the plant fiber material does not meet the requirements of cementing slurry under high temperature and high pressure.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The present invention can effectively evaluate the adaptability of plant fibers of various sizes in cement slurry under high temperature and high pressure, and the method is simple. By directly testing the crystal structure, chemical structure and thermal stability of plant fibers under different curing conditions, the adaptability of plant fibers can be intuitively and accurately obtained, which provides data support for the application of plant fibers in oil and gas well cementing engineering and is of great significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The figure is a flow chart of the method of the present invention.

[0034] Figure 2 This is the appearance of plant fibers in the filtrate of uncured cement slurry.

[0035] Figure 3 This is the appearance of plant fiber in cement slurry filtrate at a curing temperature of 90°C and a curing time of 14 days.

[0036] Figure 4 This is the appearance of plant fiber in cement slurry filtrate at a curing temperature of 90°C and a curing time of 28 days.

[0037] Figure 5 This is the appearance of plant fiber in cement slurry filtrate at a curing temperature of 90°C and a curing time of 60 days.

[0038] Figure 6 This is the appearance of plant fiber in cement slurry filtrate at a curing temperature of 150°C and a curing time of 14 days.

[0039] Figure 7 This is the appearance of plant fiber in cement slurry filtrate with curing temperature of 150℃ and curing time of 28 days.

[0040] Figure 8 This is the appearance of plant fiber in cement slurry filtrate at curing temperature of 150℃ and curing time of 60 days.

[0041] Fig. 9 This is the relative mass change diagram of the plant fiber mass loss curve in cement slurry filtrate at a curing temperature of 90°C and a curing time of 14, 28 and 60 days.

[0042] Fig.10This is the relative mass derivative change diagram of the plant fiber mass loss curve in cement slurry filtrate at a curing temperature of 90°C and curing time of 14, 28 and 60 days.

[0043] Fig.11 This is the relative mass change diagram of the plant fiber mass loss curve in cement slurry filtrate at a curing temperature of 150°C and curing times of 14, 28 and 60 days.

[0044] Fig.12 This is the relative mass derivative change diagram of the plant fiber mass loss curve in cement slurry filtrate at a curing temperature of 150°C and curing times of 14, 28 and 60 days.

[0045] Fig.13 These are the X-ray diffraction test graphs of plant fibers in cement slurry filtrate at a curing temperature of 90°C and curing times of 14, 28, and 60 days.

[0046] Fig.14 These are the X-ray diffraction test graphs of plant fibers in cement slurry filtrate at a curing temperature of 150°C and curing times of 14, 28, and 60 days. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0048] The present invention provides a method for directly evaluating the adaptability of plant fibers in cement slurry under high temperature and high pressure, comprising the following steps:

[0049] Step 1, cement slurry preparation: preparing cementing cement slurry, and heating the cementing cement slurry under normal pressure;

[0050] Step 2, high temperature and high pressure dehydration instrument maintenance: transfer the cement slurry heated in step 1 to the high temperature and high pressure dehydration instrument, seal it and then heat it;

[0051] Step 3, filtrate preparation: remove and collect the filtrate in the cementing slurry in the high temperature and high pressure dehydration instrument after reheating;

[0052] Step 4, putting the plant fiber material into the high temperature and high pressure curing tank, pouring the filtrate into the plant fiber material to wet it, and sealing the high temperature and high pressure curing tank;

[0053] Step 5, high temperature curing in a muffle furnace: placing the sealed high temperature and high pressure curing tank in a muffle furnace for curing;

[0054] Step 6, filtration and washing: taking out the high temperature and high pressure curing tank after curing from the muffle furnace, cooling it to room temperature, pouring out the mixture of the plant fiber material and the filtrate inside, and filtering and washing out the plant fiber material;

[0055] Step 7, dehydration: vacuum freezing to remove free water in the plant fiber material to obtain the cured plant fiber material;

[0056] Step 8, plant fiber structure test: using an X-ray diffractometer to collect the X-ray diffraction spectrum of the plant fiber material after curing, and calculating the crystallinity of the plant fiber material after curing;

[0057] Step 9, thermal stability test: using a thermogravimetric analyzer to test the mass loss curve of the plant fiber material after curing;

[0058] Step 10, determination: compare the X-ray diffraction pattern and crystallinity obtained in step 8 and the mass loss curve obtained in step 9 with the X-ray diffraction pattern, crystallinity and mass loss curve of the plant fiber material that has not been treated with high pressure and high temperature, and evaluate whether the plant fiber material meets the requirements of cement slurry under high temperature and high pressure.

[0059] In the step 1, cementing slurry is prepared according to GB / T19139-2012 standard; preferably, the cementing slurry is heated by a normal pressure viscosifier, the heating temperature is room temperature to 90° C., and the heating time is 10 to 30 minutes, preferably 20 minutes.

[0060] In the step 2, glass fiber filter paper or high temperature resistant filter paper is pre-covered on the metal filter screen at the bottom of the high temperature and high pressure dehydration instrument; when the experimental temperature of the reheating is room temperature to 100°C, the cementing cement slurry heated in step 1 is poured into the high temperature and high pressure dehydration instrument, sealed, and cured for 30 to 90 minutes, preferably 60 minutes; when the experimental temperature of the reheating is 100 to 210°C, the cementing cement slurry heated in step 1 is poured into the high temperature and high pressure dehydration instrument, sealed, and a pressure greater than the saturated vapor pressure of water at the experimental temperature (0.1 to 2 MPa) is injected into the high temperature and high pressure dehydration instrument to avoid filtrate loss caused by boiling of cement slurry at high temperature, and cured for 30 to 90 minutes, preferably 60 minutes.

[0061] In the step 3, the filtrate hole at the bottom of the high-temperature and high-pressure dehydration instrument is opened, and nitrogen or inert gas is introduced at the top of the high-temperature and high-pressure dehydration instrument to make its internal pressure reach 0.1~6.9MPa, and the filtrate in the cementing cement slurry is removed and collected by pressure difference, and the filtrate is collected by a beaker or other capacity instrument; preferably, when the reheating experimental temperature is 100~210°C, a condenser is connected to the filtrate hole at the bottom of the high-temperature and high-pressure dehydration instrument to avoid evaporation of the cementing cement slurry filtrate, so as to condense and collect the filtrate. In the step 4, the amount of plant fiber material input is 1-2g, the amount of filtrate poured into the cementing cement slurry is 100~150mL, and a back pressure valve is installed on the back of the high-temperature and high-pressure curing tank, which automatically releases pressure when the internal pressure of the tank body is higher than 5MPa. The preferred volume of the high-temperature and high-pressure curing tank is 270mL and the tank body thickness is 7.5mm.

[0062] In step 5, the curing temperature and time of the muffle furnace are matched with the cementing engineering environment. Preferably, the curing temperature of the muffle furnace is room temperature to 210° C., and the curing time is 0 to 180 days, more preferably 1-180 days, and further preferably 14-60 days.

[0063] In step 6, a vacuum filter is used to filter out the filtrate in the mixture to obtain a plant fiber material. During the filtration process, distilled water is continuously used for washing until the pH value of the filtrate drops to 7 to ensure that the filtrate in the plant fiber material is cleaned.

[0064] In step 7, a vacuum freeze dryer is preferably used to remove free water from the plant fiber material.

[0065] In step 8, the operating voltage of the X-ray diffractometer is 40 kV, the operating current is 30 mA, the scanning rate is 0.02° / s, and the scanning range is 5-40°. The crystallinity is calculated according to the Segal empirical model. The Segal empirical model is ,in I (002) is the maximum intensity of the lattice diffraction angle, I am is the scattered intensity of the non-crystalline background diffraction.

[0066] In step 9, the heating rate of the thermogravimetric analyzer is 10°C / min, and the test temperature is 40-400°C.

[0067] In the step 10, if the X-ray diffraction pattern and crystallinity obtained in step 8 and the mass loss curve obtained by testing in step 9 are respectively the same or similar to the X-ray diffraction pattern, crystallinity and mass loss curve of the plant fiber material that has not been treated with high pressure and high temperature, the plant fiber material meets the requirements of cement slurry for cementing under high temperature and high pressure; otherwise, the plant fiber material does not meet the requirements of cement slurry for cementing under high temperature and high pressure.

[0068] The X-ray diffraction pattern and mass loss curve described in the present invention are the same, which means that the X-ray diffraction pattern or mass loss curve of the cured plant fiber material is compared with the X-ray diffraction pattern or mass loss curve of the uncured plant fiber material, and the curve trends are the same, that is, they are determined to be similar; the specific value of the crystallinity fluctuates by no more than 10%, that is, it is determined to be similar. The mass loss curve specifically includes a relative mass change graph of the mass loss curve and a relative mass derivative change graph of the mass loss curve, and the X-ray diffraction pattern is specifically manifested as an X-ray diffraction pattern test graph.

[0069] In step 10, the determination also includes comparing the appearance of the plant fiber material, and the appearance includes at least macroscopic structure and color. If the appearance of the plant fiber material treated with high pressure and high temperature is not changed compared with the plant fiber material not treated with high pressure and high temperature, it can also be determined that the plant fiber material meets the requirements of cement slurry for cementing under high temperature and high pressure.

[0070] Example 1

[0071] This example uses the method of the present invention to examine the adaptability of the same cotton fiber under different high-temperature curing conditions.

[0072] At present, my country's oil and gas exploration and development is mainly in the middle and deep layers of 4000~7500m, and the bottom hole temperature is mostly distributed in the range of 90~150℃. Therefore, 90℃ and 150℃ are selected to evaluate the adaptability of plant fiber materials at this temperature. Specifically:

[0073] Step 1, cement slurry preparation: prepare cementing slurry according to GB / T19139-2012 standard, use normal pressure thickener to heat cementing slurry, heating temperature is 90°C, heating time is 20min;

[0074] Step 2, high temperature and high pressure dehydration instrument maintenance: pre-cover the glass fiber filter paper on the metal filter screen at the bottom of the high temperature and high pressure dehydration instrument; transfer the cementing slurry heated in step 1 to the high temperature and high pressure dehydration instrument, seal it, and reheat it. The reheating temperature is 90° C. and the heating time is 60 minutes;

[0075] Step 3, filtrate preparation: open the filtrate hole at the bottom of the high-temperature and high-pressure dehydration instrument, introduce nitrogen gas at the top of the high-temperature and high-pressure dehydration instrument to make its internal pressure reach 6.9MPa, use the pressure difference to remove and collect the filtrate in the cementing slurry, and use a beaker or other volumetric instrument to collect the filtrate;

[0076] Step 4: Add plant fiber materials: Add cotton fiber into a high-temperature and high-pressure curing tank, pour in the filtrate to soak the bamboo fiber, and seal the high-temperature and high-pressure curing tank; 100 mL of filtrate should be poured into every 1 gram of cotton fiber to soak it;

[0077] Step 5, high temperature curing in a muffle furnace: placing the sealed high temperature and high pressure curing tank in a muffle furnace for curing according to the curing conditions shown in Table 1;

[0078] Step 6, filtration and washing: take out the high temperature and high pressure curing tank after curing from the muffle furnace, cool it to room temperature, pour out the mixture of cotton fiber and filtrate inside, use a vacuum filter to filter out the filtrate in the mixture to obtain cotton fiber, and continue to use distilled water to wash during the filtration process until the pH value of the filtrate drops to 7 to ensure that the filtrate in the bamboo fiber is cleaned;

[0079] Step 7, dehydration: vacuum freezing to remove free water in the cotton fiber to obtain cured cotton fiber;

[0080] Step 8, cotton fiber structure test: X-ray diffraction patterns of the cured cotton fibers were collected using an X-ray diffractometer, and the crystallinity of the cured cotton fibers was calculated according to the Segal empirical model. The operating voltage of the X-ray diffractometer was 40 kV, the operating current was 30 mA, the scanning rate was 0.02° / s, the scanning range was 40°, and the Segal empirical model was ,in I (002) is the maximum intensity of the lattice diffraction angle, I am is the scattering intensity of the non-crystalline background diffraction;

[0081] Step 9, thermal stability test: using a thermogravimetric analyzer to test the mass loss curve of the cotton fiber after curing, the heating rate of the thermogravimetric analyzer is 10°C / min, and the test temperature is 40-400°C;

[0082] Step 10: Determination: Compare the X-ray diffraction pattern and crystallinity obtained in step 8 and the mass loss curve obtained in step 9 with the X-ray diffraction pattern, crystallinity and mass loss curve of cotton fiber that has not been treated with high pressure and high temperature, respectively, to evaluate whether the cotton fiber meets the requirements of cement slurry under high temperature and high pressure.

[0083] Table 1 Different curing conditions of cotton fiber

[0084]

[0085] The results are attached Figure 3-14 shown.

[0086] 1. Macrostructure and color results of cotton fibers under different curing conditions

[0087] Figure 2 Figure 2 shows cotton fibers in the filtrate of uncured cement slurry. Figure 3 , Figure 4 and Figure 5The pictures of cotton fibers cured in cement slurry filtrate after curing in muffle furnace at 90℃ for 14 days, 28 days and 60 days respectively; Figure 3 , Figure 4 and Figure 5 It can be seen that there is no obvious change in the macrostructure and color of cotton fibers in the cement slurry filtrate after curing at 90℃ for 14 days, 28 days and 60 days compared with no curing.

[0088] Figure 6 , Figure 7 and Figure 8 The pictures of cotton fibers cured in cement slurry filtrate at 150℃ for 14 days, 28 days and 60 days in muffle furnace. Figure 6 , Figure 7 and Figure 8 It can be seen that when the curing time increases, the color of the cotton fiber changes from white to black when cured at 150°C for 14 days, 28 days and 60 days compared with no curing. When the curing time reaches 60 days, the cotton fiber completely turns black, and its macroscopic structure has changed from the original fiber structure to a powder structure.

[0089] 2. Thermal stability results of cotton fibers under different curing conditions

[0090] Fig. 9 and Fig.10 The relative mass change graph and relative mass derivative change graph of the mass loss curve after curing in a muffle furnace at 90°C for 14 days, 28 days and 60 days, respectively. Fig.11 and Fig.12 The relative mass change graph and relative mass derivative change graph of the mass loss curve after curing in a muffle furnace at 150°C for 14 days, 28 days and 60 days, respectively. Figures 9 to 12 Uncured cotton fibers were placed in the cement slurry filtrate as the thermogravimetric control group.

[0091] Depend on Fig. 9 and Fig.10 It can be seen that compared with no curing at 90°C for 14 days, 28 days and 60 days, the thermogravimetric test results (relative mass change of the mass loss curve and the relative mass derivative change of the mass loss curve) did not change significantly, and its thermal decomposition temperature did not change significantly, proving that the thermal stability of cotton fiber under this condition is good.

[0092] Depend on Fig.11 and Fig.12 It can be seen that compared with no curing, the thermogravimetric test results (relative mass change of the mass loss curve and the relative mass derivative change of the mass loss curve) of the cotton fibers cured at 150°C for 14 days, 28 days and 60 days have changed significantly, and the thermal decomposition temperature has decreased significantly with the increase of curing time, proving that the thermal stability of cotton fibers is significantly destroyed under this condition.

[0093] 3. Crystal structure results of plant fibers under different curing conditions

[0094] Fig.13 This is the X-ray diffraction pattern test diagram after curing in a muffle furnace at 90°C for 14 days, 28 days and 60 days. Fig.14 This is the X-ray diffraction pattern test diagram after curing in a muffle furnace at 150°C for 14 days, 28 days and 60 days. Fig.13 and Fig.14 Uncured cotton fibers in cement slurry filtrate were set in the samples as the diffraction control group.

[0095] Depend on Fig.13 It can be seen that there is no significant change in the X-ray diffraction test results when the fibers are cured at 90°C for 14 days, 28 days and 60 days compared with those without curing. In addition, the main crystal structure in the cotton fiber is crystalline cellulose, and its crystal structure is not significantly destroyed under this curing condition.

[0096] Depend on Fig.14 It can be seen that the X-ray diffraction test results changed when the cotton fibers were cured at 150°C for 14 days, 28 days and 60 days compared with those without curing. When the curing time reached 60 days, the crystal structure of the cotton fibers was almost completely destroyed. This is because cement slurry is a strong alkaline and highly mineralized solution, and at 150°C, the cellulose fibers will undergo alkaline hydrolysis and peeling reactions, which will destroy the crystal structure of the cellulose fibers.

[0097] At the same time, the crystallinity of cotton fibers in cement slurry filtrate cured at 90 °C for 14 days, 28 days and 60 days, and at 150 °C for 14 days, 28 days and 60 days was calculated. The cotton fibers in the uncured cement slurry filtrate were also set as the crystallinity control group, as shown in Table 2.

[0098] Table 2 Crystallinity of cotton fibers under different curing conditions

[0099]

[0100] The results shown in Table 2 were calculated using Segal's empirical formula. The results showed that when cured at 150°C for 60 days, the crystallinity of the cotton fiber decreased from 0.69 to almost 0, and the long-term high temperature exposure seriously destroyed its crystallinity.

[0101] Based on the above evaluation results, it can be found that cotton fibers mainly composed of crystalline cellulose can meet the requirements of long-term service in a maintenance environment of 90°C in cementing cement slurry, but it is difficult to adapt to a high temperature environment of 150°C, which is consistent with existing experience or experimental data. Therefore, the method for directly evaluating the adaptability of plant fibers in cement slurry under high temperature and high pressure described in the present invention can effectively evaluate the adaptability of plant fibers of various sizes in cement slurry under high temperature and high pressure, and provide data support for the application of plant fibers in oil and gas well cementing projects and is of great significance.

[0102] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields is also included in the patent protection scope of the present invention.

Claims

1. A method for directly evaluating the adaptability of plant fibers in cement slurry under high temperature and high pressure, characterized in that: The following steps are involved: Step 1, preparing cementing slurry, and heating the cementing slurry under normal pressure; Step 2, transferring the cement slurry heated in step 1 to a high temperature and high pressure dehydration instrument, sealing it and then heating it; Step 3, removing and collecting the filtrate in the cementing slurry in the high temperature and high pressure dehydration instrument after reheating; Step 4: putting the plant fiber material into a high temperature and high pressure curing tank, pouring the filtrate into the plant fiber material to wet it, and sealing the high temperature and high pressure curing tank; Step 5, placing the sealed high temperature and high pressure curing tank in a muffle furnace for curing; Step 6, taking out the high temperature and high pressure curing tank after curing from the muffle furnace, cooling it to room temperature, pouring out the mixture of the plant fiber material and the filtrate inside, and filtering and washing out the plant fiber material; Step 7: vacuum freezing to remove free water in the plant fiber material to obtain the cured plant fiber material; Step 8, using an X-ray diffractometer to collect an X-ray diffraction pattern of the cured plant fiber material, and calculating the crystallinity of the cured plant fiber material; Step 9, using a thermogravimetric analyzer to test the mass loss curve of the plant fiber material after curing; Step 10, comparing the X-ray diffraction pattern and crystallinity obtained in step 8 and the mass loss curve obtained in step 9 with the X-ray diffraction pattern, crystallinity and mass loss curve of the plant fiber material that has not been treated with high pressure and high temperature, to evaluate whether the plant fiber material meets the requirements of cement slurry for cementing under high temperature and high pressure; In the step 4, the amount of plant fiber material input is 1-2 g, the amount of filtrate poured into the cementing slurry is 100-150 mL, and the plant fiber material is any one of bamboo fiber, cotton fiber, sisal fiber, wood fiber or crop straw fiber; In step 5, the curing temperature and time of the muffle furnace are matched with the cementing engineering environment, the curing temperature of the muffle furnace is room temperature to 210° C., and the curing time is 0 to 180 days; In the step 10, if the X-ray diffraction pattern and crystallinity obtained in step 8 and the mass loss curve obtained by testing in step 9 are respectively the same as the X-ray diffraction pattern, crystallinity and mass loss curve of the plant fiber material that has not been treated with high pressure and high temperature, the plant fiber material meets the requirements of cement slurry for cementing under high temperature and high pressure; otherwise, the plant fiber material does not meet the requirements of cement slurry for cementing under high temperature and high pressure.

2. A method for directly evaluating the adaptability of plant fibers in cement slurry under high temperature and high pressure according to claim 1, characterized in that: In the step 1, cementing slurry is prepared according to GB / T19139 standard; and the cementing slurry is heated by a normal pressure thickener at a temperature of room temperature to 90° C. for a heating time of 10 to 30 minutes.

3. A method for directly evaluating the adaptability of plant fibers in cement slurry under high temperature and high pressure according to claim 2, characterized in that: The heating time is 20 minutes.

4. The method for directly evaluating the adaptability of plant fibers in cement slurry under high temperature and high pressure according to claim 1, characterized in that: In step 2: When the reheating experimental temperature is room temperature to 100°C, pour the cement slurry heated in step 1 into the high temperature and high pressure dehydration instrument, seal it, and maintain it for 30 to 90 minutes; When the reheating test temperature is 100-210°C, pour the cement slurry heated in step 1 into the high-temperature and high-pressure dehydration apparatus, seal it, and inject a pressure greater than the saturated vapor pressure of water at the test temperature into the high-temperature and high-pressure dehydration apparatus, and maintain it for 30-90 minutes.

5. A method for directly evaluating the adaptability of plant fibers in cement slurry under high temperature and high pressure according to claim 4, characterized in that: When the reheating experimental temperature is room temperature to 100°C, pour the cement slurry heated in step 1 into the high temperature and high pressure dehydration instrument, seal it, and maintain it for 60 minutes; When the reheating experimental temperature is 100-210°C, pour the cement slurry heated in step 1 into the high temperature and high pressure dehydration apparatus, seal it, and inject a pressure greater than the saturated vapor pressure of water at the experimental temperature into the high temperature and high pressure dehydration apparatus, and maintain it for 60 minutes.

6. A method for directly evaluating the adaptability of plant fibers in cement slurry under high temperature and high pressure according to claim 4, characterized in that: In the step 3, the filtrate hole at the bottom of the high-temperature and high-pressure dehydration instrument is opened, and nitrogen or inert gas is introduced into the top of the high-temperature and high-pressure dehydration instrument to make the internal pressure reach 0.1-6.9 MPa, and the filtrate in the cementing cement slurry is removed and collected by using the pressure difference; When the reheating experimental temperature is 100~210°C, a condenser is connected to the filtrate hole at the bottom of the high temperature and high pressure dehydration apparatus to condense and collect the filtrate.

7. The method for directly evaluating the adaptability of plant fibers in cement slurry under high temperature and high pressure according to claim 1, characterized in that: The maintenance time is 1-180 days.

8. The method for directly evaluating the adaptability of plant fibers in cement slurry under high temperature and high pressure according to claim 1, characterized in that: The curing time is 14-60 days.

9. The method for directly evaluating the adaptability of plant fibers in cement slurry under high temperature and high pressure according to claim 1, characterized in that: In the step 6, a vacuum filter is used to filter out the filtrate in the mixture to obtain the plant fiber material, and distilled water is continuously used for washing during the filtration process until the pH value of the filtrate drops to 7.

10. The method for directly evaluating the adaptability of plant fibers in cement slurry under high temperature and high pressure according to claim 1, characterized in that: In step 8, the operating voltage of the X-ray diffractometer is 40 kV, the operating current is 30 mA, the scanning rate is 0.02° / s, and the scanning range is 5-40°. The crystallinity is calculated according to the Segal empirical model. The Segal empirical model is ,in I (002) is the maximum intensity of the lattice diffraction angle, I am is the scattered intensity of the non-crystalline background diffraction.

11. A method for directly evaluating the adaptability of plant fibers in cement slurry under high temperature and high pressure according to claim 1, characterized in that: In step 9, the heating rate of the thermogravimetric analyzer is 10°C / min, and the test temperature is 40-400°C.

Citation Information

Patent Citations

  • Method for in-situ characterization of performance degradation of plant fibers in cement matrix environment

    CN113049382A

  • A method for quantitatively characterizing mineralization degree of plant fibers

    CN110082375A

  • Polyphenylene sulfide fiber failure quantitative judgment method

    CN111537387A